An examination of the relationship between perceived leadership and stress in hospital employees - Baysak, Birol (My University, 2015)
Bu çalışma, hastane çalışanlarının algılamış oldukları liderlik tarzı ve stres arasındaki ilişkinin tespit edilmesi için İstanbul’da kamu hastanelerinde çalışan 312 hastane çalışanını incelemiştir. Algılanan liderlik 36 soru ve 3 ana faktörden oluşan Çok Faktörlü Liderlik Anketi ile ölçülmüştür. Her ana faktörün alt faktörleri bulunmaktadır. “Dönüşümcü Liderlik” alt faktörleri; “Karizmatik-İlham verici lider”, “Entelektüel uyarım” ve “Bireysel Destek” ten oluşmaktadır. İkinci ana faktör, “Sürdürümcü Liderlik” faktörü de “Ödüle bağlı”, Aktif ve Pasif” olmak üzere 3 “ üç alt faktörden oluşmaktadır. Üçüncü ve son ana faktör ise “Serbestlik Tanıyan” Liderliktir. Çalışanların stres seviyesi Algılanan Stres Ölçeği kullanılarak incelenmiştir. Araştırmanın evreni 2520, örneklem grubu 333 hastane çalışanı olarak hesaplanmıştır. Araştırmaya katılmak üzere 500 kişiye anket gönderilmiş, 350 kişi cevaplandırmıştır. Cevaplandırılan anketlerden 38 adedi tam olarak doldurulmadığı için elenmiştir. Bu araştırmanın amacı İstanbul’da görev yapmakta olan hastane çalışanlarının algılamış oldukları liderlik ve stres seviyeleri arasındaki ilişkiyi ve boyutunu incelemektir. Elde edilen veriler sosyal bilimlerde istatistik paket SPSS” ile incelenmiş, bağımsız gruplar t testi, tek yön varyans analizi (ANOVA) ve regresyon analizi uygulanmıştır. Araştırmanın sonuçları daha önceki liderlik ve stres konulu araştırmalar ile benzerlik göstermiştir. Algılanan Liderlik, Algılanan Stres, Sağlık Hizmeti, Hastane Çalışanı

This study examined 312 nonprofit hospital employees in Istanbul in order to determine if an association exist between hospital employees’ perceived leadership style and perceived stress levels. Perceived leadership was assessed with Multifactor Leadership Questionnaire (MLQ), which has 36 questions and 3 main factors. Each main factor has sub factors. Transformational leadership sub factors are, Charismatic-Inspirational Leadership, Intellectual Simulation and Individualized Consideration. As to second main factor transactional leadership, there are also three sub factor named as Contingent reward, Management by Exception active and Management by exception passive. The third last main factor is the Passive/ Avoidant leadership. Stress levels of the participants were assessed by The Perceived Stress Scale. Target population of the study was estimated 2520 nonprofit hospital employees. The sample of the study were estimated 333 nonprofit hospital employees. 500 nonprofit hospital employees were invited to participate to study; 350 were responded, 38 ones were eliminated because of deficiency on surveys. The purpose of the quantitative study was to examine whether, and to what extent, relationship existed between perceived stress and perceived leadership style of hospital employees in İstanbul Turkey. Gathered data analyzed through the SPSS statistical packaged software and independent t- tests, one way ANOVA, regression analysis were conducted. Study results indicated similarity with former studies about leadership and stress. Perceived Leadership, Perceived Stress, Healthcare, Hospital Employee
Keywords: Araştırma; Hastane çalışanları; Hastaneler, Devlet; Liderlik; Psikolojik yönleri; Türkiye; Yönetim